A sacred adventure in lands that became holy: Diego de Ocaña, O.S.H., 1599-1608 - Mills, Kenneth (2019)
In the present essay, I delve into one of the fundamental inspirations behind an untitled, illustrated manuscript by Diego de Ocaña, an alms-collector travelling on behalf of the miraculous advocation of Our Lady of Guadalupe de Extremadura in the Villuercas mountains: the manuscript now known as the Relación del viaje de fray Diego de Ocaña por el Nuevo Mundo (1599-1608). Because the manuscript did not circulate widely and long remained unpublished, and because it has usually been fragmentarily employed if not marginalized from the chronicling canon for one reason or another, study of its whole remains in its infancy. It has long been known that Ocaña was a reader; and it has been correctly proposed that the appreciation of Ocaña’s evident familiarity with certain romances de caballería, with Alonso de Ercilla’s La Araucana and with cronistas such as Alvár Núñez Cabeza de Vaca would be crucial to interpreting his manuscript. But, beyond direct citations (which are few, both in Ocaña’s case and by other contemporary authors), the broader readerliness of Diego de Ocaña has been underestimated. Most oddly of all given his religious vocation, his more spiritual influences have been neglected. I ask in this essay what other kinds of texts in which matters and things deemed sacred and notable were central, were available to him and expected by his principal readers. I ask how such readings may have focussed and enabled Ocaña’s ways of seeing, imagining and portraying American lands, people, and phenomena, especially those which he and others needed to be sacred and notable. I suggest that a fundamental inspiration for Diego de Ocaña’s presentation of himself as a sacred adventurer and reporter lay in the richly honed, and thus highly re-generative, repertoires offered by late medieval and early modern accounts of pilgrimages to the Holy Land and related sacred journeys.